2002
DOI: 10.1097/00005131-200207000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Reduction of Open-Book Pelvic Fractures by Circumferential Compression

Abstract: Objectives: To determine the efficacy and optimal application parameters of circumferential compression to reduce external rotation-type pelvic fractures. Design: Biomechanical investigation on human cadaveric specimens. Setting: Biomechanics laboratory. Intervention: Partially stable and unstable external rotation injuries of the pelvic ring (OTA classification 61-B1 and 61-C1) were created in seven human cadaveric specimens. A prototype pelvic strap was applied subsequently at three distinct transverse level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(78 citation statements)
references
References 33 publications
0
69
0
3
Order By: Relevance
“…Most, but not all, orthopaedic registrars (79.1 %) stated that they would place the binder at the level of the GT. These results show that more adequate training is required, as there is clear evidence that compression around the GT is most effective in reducing unstable open-book fractures [8,16,17]. Importantly, a misplaced binder may make a pelvic injury worse if there is a fracture through the iliac crests.…”
Section: Discussionmentioning
confidence: 95%
“…Most, but not all, orthopaedic registrars (79.1 %) stated that they would place the binder at the level of the GT. These results show that more adequate training is required, as there is clear evidence that compression around the GT is most effective in reducing unstable open-book fractures [8,16,17]. Importantly, a misplaced binder may make a pelvic injury worse if there is a fracture through the iliac crests.…”
Section: Discussionmentioning
confidence: 95%
“…Extended softtissue damage and lengthy surgical procedures complicate the decision-making process [5][6][7]. The most frequent reason for a fatal outcome is a pelvic mass haemorrhage, which can only be controlled by compression [8] with a stable pelvic ring as counter-bearing force [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the exact application location of the PCCD strongly affects the local pressure level and overall effects. Research into the transverse application level of a specific sling showed that the sling should be applied at the area of the greater trochanters and the symphysis pubis [7].…”
Section: Introductionmentioning
confidence: 99%
“…The applied pulling forces according to manufacturers application instructions differ substantially. A study on human cadaveric specimens showed the minimum strap tension required to achieve complete reduction of symphysis diastasis was 177 ± 44 N and 180 ± 50 N in the partially stable and unstable pelvis, respectively [7]. As opposed to the tension required to achieve complete reduction, there is no data available for the required tension to achieve hemostasis for initial resuscitation.…”
Section: Introductionmentioning
confidence: 99%